Pelvic Rocking Sebagai Metode Nonfarmakologis Dalam Manajemen Nyeri Persalinan Kala I - Sri Untari (Universitas Ivet, 2026)
Childbirth is a physiological process that marks the end of pregnancy. Labor pain management is an important part of modern obstetric care. The aim of this study was to examine the effectiveness of pelvic rocking in reducing the intensity of pain in the first stage of labor. One non-pharmacological method that is gaining increasing attention is the pelvic rocking technique. This study used a Systematic Literature Review (SLR). Databases searched included Google Scholar, PubMed, and ScienceDirect. This study focused on pelvic rocking in first-stage labor pain management. Based on the results of a Systematic Literature Review (SLR) of 9 studies, pelvic rocking is an effective non-pharmacological method in reducing the intensity of first-stage labor pain. All studies reported a statistically significant reduction in pain (p<0.05), with a recent meta-analysis reporting a large effect size (SMD -1.32). Pelvic rocking recommendations have the potential to be considered as part of the standard of care for intrapartum obstetrics, and standard guidelines for the implementation of pelvic rocking should be developed. It is necessary to use a more rigorous RCT design with a standardized protocol and a larger sample.